2022
DOI: 10.3390/math10060896
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Preservice Mathematics Teachers’ Culturally Responsive Teaching: A Focus on Teaching for Social Justice

Abstract: This paper reports on how 10 middle and high school preservice teachers (PSTs) designed a social justice focused lesson using the culturally responsive mathematics teaching (CRMT) tool. Results from our analysis indicate that most of the PSTs were able to select appropriate social justice topics, though not all the PSTs integrated mathematics and social justice throughout their lessons. The results show that most of the PSTs need more experience with mathematization, handling controversial discussions, and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Indeed, the lack of training programs and applications dealing with how to integrate ethnomathematics confirms this. Register et al (2022) have highlighted the importance of teacher training in planning and teaching design to promote ethnomathematics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the lack of training programs and applications dealing with how to integrate ethnomathematics confirms this. Register et al (2022) have highlighted the importance of teacher training in planning and teaching design to promote ethnomathematics.…”
Section: Discussionmentioning
confidence: 99%
“…Research on critical mathematics education has identified significant themes highlighting the role of SJM in supporting students' development of conscientização (critical consciousness) and fostering sociocultural identities and political subjectivities. Critical mathematics education also encourages action against social injustices, nurtures a sense of agency and promotes mathematical inquiry that deepens learners' understanding of sociocultural and political-economic contexts (see, for example, Ataide Pinheiro, 2022;Felton-Koestler, 2017Rankin et al, 2021;Register et al, 2022;Wright, 2016Wright, , 2021. Another crucial aspect of the epistemology of critical mathematics education concerns the definition of teaching for social justice.…”
Section: Critical Theory and Sjmmentioning
confidence: 99%
“…They need a teacher preparation program that focuses their attention on the learning of the students they are teaching ( Kilpatrick, 2016 ). They must understand mathematics, teaching, and pedagogy ( Register et al, 2022 ). Proper understanding of mathematical problem solving and its teaching is an essential part of the professional quality of preservice mathematics teachers and can effectively guide their future teaching of mathematical problem solving.…”
Section: Introductionmentioning
confidence: 99%